Could Brain–Computer Interface Be a New Therapeutic Approach for Body Integrity Dysphoria? - Chakraborty, Stuti; Saetta, Gianluca; Simon, Colin; Lenggenhager, Bigna; Ruddy, Kathy (Frontiers in Human Neuroscience, 2021)
Patients suffering from Body Integrity Dysphoria (BID) desire to become disabled, arising from a mismatch between the desired body and the physical body. We focus here on the most common variant, characterised by the desire for amputation of a healthy limb. In most reported cases amputation of the rejected limb entirely alleviates the distress of the condition and engenders substantial improvement in quality of life. Since BID can lead to life-long suffering, it is essential to identify an effective form of treatment that causes the least amount of alteration to the person’s anatomical structure and functionality. Treatment methods involving medications, psychotherapy and vestibular stimulation have proven largely ineffective. In this hypothesis article, we briefly discuss the characteristics, aetiology, and current treatment options available for BID before highlighting the need for new, theory driven approaches. Drawing on recent findings relating to functional and structural brain correlates of BID, we introduce the idea of Brain Computer Interface (BCI)/neurofeedback approaches to target altered patterns of brain activity, promote re-ownership of the limb and/or attenuate stress and negativity associated with the altered body representation.